Characteristics of Adolescents at Risk for Excess Weight Gain During Pregnancy [18R]. (May 2016) - Chang, Tammy; Moniz, Michelle; Plegue, Melissa; Sen, Ananda; Davis, Matthew; Richardson, Caroline
Abstract : INTRODUCTION: Excess weight gain during pregnancy is a serious health concern affecting a significant proportion of pregnant US adolescents. This study aimed to characterize adolescents at highest risk for excess weight gain during pregnancy. METHODS: Using a nationally representative longitudinal database, The Fragile Families and Child Wellbeing Study, we identified mothers age 15–24 at time of birth. Institute of Medicine guidelines were used to categorize each mother as gaining less than recommended, within recommended, or more than recommended during pregnancy. Multinomial logistic regression models were performed, with weight gain category as the outcome, controlling for confounders including age, race/ethnicity, federal poverty level (FPL), health status, and pre-pregnancy BMI. RESULTS: Among our weighted sample (n=1, 248, N=241, 232), the mean (SD) age was 21 (3) years, 32% were black, 47% Hispanic, 45% with income under the FPL, 44% were overweight or obese before pregnancy, and 59% gained more than recommended during pregnancy. Multinomial logistic regression showed that Hispanics were less likely to gain more than the recommended weight compared to non-Hispanics (RR 0.39, P =.029). Adolescents who were overweight and obese before pregnancy were more likely to gain more than the recommended weight than their normal weight peers (RR 3.82, P =.011; RR 3.27, P =.027). There were no other significant associations. CONCLUSION: Pre-pregnancy BMI and ethnicity are the primary factors that predict excess pregnancy weight gain among US adolescents age 15–24. Interventions and policies should focus on high-risk adolescents to prevent excess weight gain-related morbidity among these mothers and their children.